2014
DOI: 10.17576/jskm-1201-2014-06
|View full text |Cite
|
Sign up to set email alerts
|

Nutritive Value and Fatty Acids Profile of Fresh Indonesian Eel (Anguilla bicolor) and Kabayaki

Abstract: 17.68% protein, 28.29% lemak, 42.03% air, 3.93% abu dan 0.3% gentian kasar. Manakala Kabayaki mengandungi 32.70% protein, 2.39% lemak, 48.32% air, 2

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 7 publications
0
9
0
1
Order By: Relevance
“…Omega-3 content in eel oil is expected to be higher than omega-3 content in other fish oils (Widyasari et al, 2014;Ahn et al, 2015;Farah et al, 2018). For instance, a study reported by Widyasari et al (2014) shows that eel oil has 5.16% omega-3. This number is considerably higher than omega-3 in milkfish oil (Chanos chanos forsskal), which only 2.4% (Aziza, 2015).…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Omega-3 content in eel oil is expected to be higher than omega-3 content in other fish oils (Widyasari et al, 2014;Ahn et al, 2015;Farah et al, 2018). For instance, a study reported by Widyasari et al (2014) shows that eel oil has 5.16% omega-3. This number is considerably higher than omega-3 in milkfish oil (Chanos chanos forsskal), which only 2.4% (Aziza, 2015).…”
Section: Introductionmentioning
confidence: 95%
“…Eel is a type of fish that contains high protein, vitamins, and fatty acid like omega-3 (EPA and DHA) (Nafsiyah et al, 2018). Omega-3 content in eel oil is expected to be higher than omega-3 content in other fish oils (Widyasari et al, 2014;Ahn et al, 2015;Farah et al, 2018). For instance, a study reported by Widyasari et al (2014) shows that eel oil has 5.16% omega-3.…”
Section: Introductionmentioning
confidence: 99%
“…Anguilla bicolor is a very abundant eel in Indonesia [1]. Eel fish oil is known to contain vitamins, proteins, saturated fatty acids (SFA), monounsaturated fatty acids (MUFA), polyunsaturated fatty acids (PUFAs) [2], [3]. The contents of crude lipids were Anguilla bicolor is 10.5% [2], [4].…”
Section: Introductionmentioning
confidence: 99%
“…Eel fish oil is known to contain vitamins, proteins, saturated fatty acids (SFA), monounsaturated fatty acids (MUFA), polyunsaturated fatty acids (PUFAs) [2], [3]. The contents of crude lipids were Anguilla bicolor is 10.5% [2], [4]. In addition to fatty eel fish also found in almost all fish [5], [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation